Risk factors for late presentation of symptomatic uterine fibroid in urban Nigeria: A mixed method study - Ayoola J. Fakunmoju; Olufunke A. Fayehun; Oluwasomidoyin O. Bello (Women's Health)
Background: Uterine fibroids (UFs) are the most common benign tumours of the uterus and are often asymptomatic. However, there is a high incidence of symptomatic fibroids among Black women, with many presenting late for treatment. Objective: We examined the patterns and risk factors associated with the late presentation of UF in Black women. Designs: Mixed methods study design: A quantitative and qualitative approach. Methods: An interviewer-administered questionnaire was used to obtain information about the late presentation of UF from 138 women at the Gynaecology clinic of the University College Hospital, Ibadan, Nigeria. For the qualitative component, in-depth interviews were conducted with eight women experiencing symptomatic fibroids. The odds of late presentation were analysed across socio-demographic, obstetrics and clinical characteristics, along with the type of diagnosis, using logistic regression with a statistical significance level set at p  < 0.05. Qualitative data were examined through an inductive thematic analysis, focusing on emerging themes. Results: The mean age of participants was 36.80± 7.24 years, with a significant proportion (62.3%) presenting late, more than 6 months after the onset of symptoms and 65.1% having multiple UFs. Factors associated with late presentation included age (AOR = 4.000; 95% CI 0.086–0.0730), parity (AOR = 3.299; 95% CI 1.150–9.464) and presenting with subfertility or infertility (AOR = 0.070; 95% CI 0.020–0.249). The qualitative findings highlighted how situational factors such as inadequate knowledge of the condition, aversion to surgery, negligence, cultural misconception and financial constraints contributed to late presentation. Conclusion: A significant number of women, particularly older and nulliparous individuals, sought care late for symptomatic UFs. Increased sensitization and targeted educational interventions are needed to encourage early presentation and timely treatment. Implementing effective health strategies that address the reasons for late presentations will improve health outcomes for women with symptomatic fibroids.